Impact of pre-dispersal predation by red squirrels (Tamiasciurus hudsonicus) and cone insects on balsam fir (Abies balsamea) seed production in eastern Newfoundland - Boa-Antwi, Kofi, 1974- (2009)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2009. Environmental Science Includes bibliographical references (leaves 60-79); CD-ROM contains photographs; <See Accompanying Files> Predispersal seed predation is a critical factor limiting population recruitment among a number of coniferous species in natural systems. Introduced species, a major threat to biodiversity, can cause high levels of predispersal seed predation. Balsam fir (Abies balsamea) regeneration and establishment has been an ongoing challenge for land managers on the island of Newfoundland due to paucity of adult trees producing female cones, and the fact that fir recruitment requires annual seed production as there is no seed bank. This study focused on the combined impact of a mammal and a suite of insects on pre-dispersal cone and seed mortality of balsam fir through investigation of ecological impacts of non-native red squirrels (Tamiasciurus hudsonicus) and a variety of predispersal cone/seed insects on this dominant tree species. Specifically, the impact of red squirrels and cone/seed insects were compared between balsam fir stands with different disturbance types and stem densities: Intact sites with no recent history of insect-infestation; and Insect Kill sites with recent history of insect infestation, around a range of stem densities (286-3100 trees/ha). The study was conducted within Terra Nova National Park and the surrounding forest management area in the southern Bonavista Bay region of the island of Newfoundland, Canada. -- The percentage of pollen cones lost to red squirrels (3.5 ± 7.3% to 84.6 ± 9.3%), with an average loss of 47.6 ± 3.9%, was significantly higher in study sites with low balsam fir stem densities (229 ± 76 trees/ha) than in sites with high balsam fir stem densities (826 ± 189 trees/ha). Pollen cone loss to red squirrels showed no significant variation between disturbance types and among sites with respect to tree height and diameter at breast height (PBH). The percentage of seed cone loss to red squirrels (33.0 ± 15.7% to 93.5 ± 3.3%), with an average loss of 58.9 ± 15.5%, was not significantly between high and low stem density sites, nor between disturbance types. The number of female cones taken by red squirrels also did not vary among trees with respect to PBH, height and cone crop size of trees. All cones sampled in the study showed some signs of insect damage with 21.4 ± 5.9% of sampled seeds in balsam fir stands showing signs of insect infestation. However, stem densities of study sites did not significantly influence seed loss to insects among trees. Furthermore, seed loss to insects did not appear to be influenced by age class, PBH, height, and average cone size of trees. However, the proportion of viable seeds prior to seed release was stem density-dependent, and increased with increasing balsam fir stem density. -- The results of the study suggest that red squirrel and insect populations were high, and hence were ubiquitous across the landscape. The combined effect of red squirrel and cone/seed insect predation resulted in over 2/3 reduction in potential seed production in all study sites combined. This may pose challenges to natural recruitment of balsam fir in the area, and a combination of Assisted Natural Regeneration, and seedling planting should be investigated as remedial options by managers of this area.